124k views
1 vote
X + 2y = -3 x - y = -12

User BDM
by
5.2k points

2 Answers

2 votes

Answer:

(-9,3)

Explanation:

x + 2y = -3

x = -3 - 2y

x - y = -12

x = y - 12

-3 - 2y = y - 12

3y = 9

y = 3

x = 3 - 12

x = -9

User RubesMN
by
5.2k points
7 votes

Answer:

x = -9, y =3

Explanation:

x + 2y = -3

x - y = -12

Subtract to two equations to eliminate x

x + 2y = -3

-x + y = 12

---------------------

3y = 9

Divide each side by 3

3y/3 = 9/3

y = 3

Now we can find x

x-y =-12

x - 3 = -12

Add 3 to each side

x-3+3 = -12+3

x = -9

User Gaff
by
5.1k points